1998
DOI: 10.1111/j.1945-5100.1998.tb01612.x
|View full text |Cite
|
Sign up to set email alerts
|

An acid‐etch study of the Kapoeta achondrite: Implications for the argon‐36/argon‐38 ratio in the solar wind

Abstract: Abstract-Noble gases were measured in the Kapoeta achondrite by means of step-wise closed-system acidetching with H2SO3. Isotopic ratios indicate that He, Ne and Ar are primarily solar in origin, although elemental abundance ratios indicate that the He and Ne have been significantly depleted relative to the Ar. Xenon is dominated by a typical trapped meteoritic component, and the same is probably true for Kr. The initial 11% of the Ar released from the sample by acid etching has a cumulative 36Ar/38Ar ratio of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 12 publications
1
5
1
Order By: Relevance
“…It is consistent with the average SWC foil ratio of 5.4 ± 0.3 (Geiss et al, 2004) and also within the stated uncertainties (1r) of the values for coronal hole-and inter-stream-related SW (5.5 ± 0.6 and 5.6 ± 0.7) observed with SOHO/CELIAS/MTOF by Weygand et al (2001). However, it is lower than the bulk value reported by Mabry et al (2007b) of 5.501 ± 0.005 (1r) in the Genesis AloS target or values of 5.58 ± 0.03 (Becker et al, 1998) and 5.48 ± 0.05 (1r) (Benkert et al, 1993) derived from solar gas-rich meteorites and relatively recently irradiated lunar soils, respectively. Approximate implantation depth of 20 Ne according to SRIM (nm) SRIM Fig.…”
Section: Argoncontrasting
confidence: 69%
“…It is consistent with the average SWC foil ratio of 5.4 ± 0.3 (Geiss et al, 2004) and also within the stated uncertainties (1r) of the values for coronal hole-and inter-stream-related SW (5.5 ± 0.6 and 5.6 ± 0.7) observed with SOHO/CELIAS/MTOF by Weygand et al (2001). However, it is lower than the bulk value reported by Mabry et al (2007b) of 5.501 ± 0.005 (1r) in the Genesis AloS target or values of 5.58 ± 0.03 (Becker et al, 1998) and 5.48 ± 0.05 (1r) (Benkert et al, 1993) derived from solar gas-rich meteorites and relatively recently irradiated lunar soils, respectively. Approximate implantation depth of 20 Ne according to SRIM (nm) SRIM Fig.…”
Section: Argoncontrasting
confidence: 69%
“…Benkert et al, 1993), at least in samples like 71501 which collected their solar wind relatively recently. A 36 Ar/ 38 Ar value of 5.58 ± 0.02 previously obtained from the gas-rich meteorite Kapoeta by a similar in-vacuo etch technique (Becker et al, 1998) as used for lunar samples is higher than the Genesis DOS and lunar values. We consider it unlikely that this small difference indicates a longterm variability of the Ar isotopic composition in the solar wind.…”
Section: Comparison With Previous Solar Wind Data -Isotope Compositionmentioning
confidence: 97%
“…7), Ott et al (1985a,b) suggested that these ureilitic noble gases must be closely related to the primordial Q noble gases, although they reside in achondritic, heavily differentiated and partly shocked meteorites (Goodrich, 1992). Component Xe-Q has been also found in other achondrite classes such as lodranites, acapulcoites, brachinites, and even the solar gas-rich howardite Kapoeta (e.g., Eugster and Weigel, 1993;McCoy et al, 1996;Swindle et al, 1998;Becker et al, 1998). Few data are available for Kr-Q and related components.…”
Section: Q-gases In Chondrites and Ureilitesmentioning
confidence: 99%